2012
DOI: 10.1007/s11605-012-2034-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Oncological Outcomes of Limited Duodenal Resection in Patients with Primary Nonmetastatic Duodenal GIST

Abstract: When technically feasible, limited resection should be considered a reliable and curative option for duodenal GIST achieving satisfactory disease-free survival. The technical feasibility is guided by the tumor size, possible adjacent organ involvement, and its exact anatomical location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
22

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 31 publications
3
9
0
22
Order By: Relevance
“…Furthermore, PD was significantly associated with a longer operation time and a longer hospital stay compared to LR. Collectively, these data indicate that LR might be a reliable and curative option for a significant subset of patients with duodenal GIST, which is in accordance with the report of El-Gendi [18]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, PD was significantly associated with a longer operation time and a longer hospital stay compared to LR. Collectively, these data indicate that LR might be a reliable and curative option for a significant subset of patients with duodenal GIST, which is in accordance with the report of El-Gendi [18]. …”
Section: Discussionsupporting
confidence: 91%
“…This is similar to previous reports, which showed that the DFS rate at 1 to 3 years after a complete surgical resection, for all kinds of resection, varies from 86% to 100% [8,13,16,18]. Prognosis and recurrence are mainly dependent on tumor biology, which is determined by size and mitotic index (Fletcher scale) [19].…”
Section: Discussionsupporting
confidence: 89%
“…Although pancreaticoduodenectomy is generally safe and associated with low mortality in specialized centers, its associated morbidity remains. 11, 12 Here, we analyze the 20-year experience of the surgical management of DGIST of 2 referral centers, including technical aspects as well as short- and long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…These systems are di cult to solve analytically.In this paper we consider the systems of linear functional di erential equations [1][2][3][4][5][6][7][8][9] including the term y(αx + β) and advance-delay in derivatives of y . To obtain the approximate solutions of those systems, we present a matrixcollocation method by using Müntz-Legendre polynomials and the collocation points.…”
Section: Introductionmentioning
confidence: 99%
“…In physics, chemistry, biology and engineering, a lot of problems are modelled by di erential equations, delay differential equations [10][11][12][13] and their systems [1][2][3][4][5][6][7][8][9][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%